2019
DOI: 10.1111/jrh.12388
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to Change and Treatment Participation Among Syringe Service Program Utilizers in Rural Kentucky

Abstract: Purpose Kentucky experiences a disproportionate burden of substance use disorder (SUD), particularly in rural areas of the state. Multiple factors increase vulnerability to SUD and limit access to services in rural communities. However, the recent implementation and expansion of syringe service programs (SSPs) in rural Kentucky may provide a leverage point to reach at‐risk people who inject drugs (PWID). Methods Data were collected as part of an ongoing NIDA‐funded study designed to examine uptake of SSPs amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
(105 reference statements)
0
13
0
Order By: Relevance
“…37 Additionally, researchers found that about half of their sample of 186 syringe service program attendees in rural Kentucky regularly utilize such services. 38 This finding signals a possible demand in rural areas for syringe exchange programs. Future studies may want to include a wider variety of options than the ones considered here.…”
Section: Discussionmentioning
confidence: 97%
“…37 Additionally, researchers found that about half of their sample of 186 syringe service program attendees in rural Kentucky regularly utilize such services. 38 This finding signals a possible demand in rural areas for syringe exchange programs. Future studies may want to include a wider variety of options than the ones considered here.…”
Section: Discussionmentioning
confidence: 97%
“…[10][11][12] Yet identifying additional modifiable characteristics that can be leveraged to enhance motivation is especially relevant for improving clinical outcomes for PWID. 6,35 In this analysis, we found that more severe opioid withdrawal was associated with decreased motivation to use clean needles. Withdrawal is a complex neurobiological phenomenon that may dampen motivation and shift an individual's attention to relieving uncomfortable symptoms.…”
Section: Discussionmentioning
confidence: 66%
“…[2][3][4] Motivation is an important step in changing substance use patterns and in engaging in treatment. 5,6 Several studies including PWID suggest that medical hospitalizations are associated with heightened motivation to seek substance use treatment. 7,8 Internal (e.g., concerns about one's own health) and external factors (e.g., family concerns) have been associated with increased motivation for substance use treatment.…”
Section: Introductionmentioning
confidence: 99%
“…21 For example, limited public transportation availability in geographically remote rural areas, a feature of the physical environment, may restrict the accessibility of SSP services; and high drug-related stigma in small, tight-knit rural communities, a feature of the social environment, may increase PWID reluctance to enroll in local SSPs. 14,15,[22][23][24][25] This analysis assesses the extent to which 5 of the…”
Section: Introductionmentioning
confidence: 99%
“…Rural is defined as scoring a 7 or higher on the RUCC and having at least 2/3 of the population residing in a rural area as reported by the US Census Bureau 21 . For example, limited public transportation availability in geographically remote rural areas, a feature of the physical environment, may restrict the accessibility of SSP services; and high drug‐related stigma in small, tight‐knit rural communities, a feature of the social environment, may increase PWID reluctance to enroll in local SSPs 14,15,22–25 …”
Section: Introductionmentioning
confidence: 99%